KETERLIBATAN BLACKSMITH INSTITUTE DALAM IMPLEMENTASI THE BASEL CONVENTION TERHADAP PENANGANAN E-WASTE DI GHANA TAHUN 2013-2015 - Sarah Adharaisa; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research discusses about electronic waste (e-waste) heap in Ghana which comes from the whole world which has given negative impacts for humans and ecosystems around garbage stacked and processed. Despite having signed the agreement of The Basel Convention which regulates about export ban of e-waste, but around 500 containers contain obsolete electronics landed in Agbogbloshie, Ghana every month. Ineffectiveness of efforts to address e-waste, has invited non-party state to contribute in e-waste management, one of non-party is Blacksmith Institute.The methode which is used in this research is qualitative research methods descriptively. As this research interprets related conditions with the problems and develops the data obtained from various sources, such as books, journal and articles on the official website.The purpose of this research is to give the consciousness on using technology sustainability with environmental conservation because in this globalization era, the electric and eletronic equipment (EEE) demand are more increasing which are caused the result of the production rest is also getting bigger, moreover the end-of-life of the EEE is not often managed properly.Keywords: e-waste, Ghana, Blacksmith Institute